RETRACTED: From Psychology Management Innovation and Education Reform in the Digital Age: Role of Disruptive Technologies - Bao, Lin; Xu, Tian (Frontiers in Psychology, 2022)
The main body of colleges and universities, the effect of college teaching management is an important standard to test the quality of college teaching management and affects the development of college teaching management. However, the management mechanism system used by traditional colleges and universities is difficult to meet the needs of the innovation of the new talent training mode of higher vocational education. The construction of the new micro level teaching organization inevitably requires the management practice, structure, process and technology at the medium and macro levels to adapt to it. However, at present, there are many mismatches in the internal and external administrative system of Higher Vocational Colleges in China, such as low administrative efficiency, generalization of administrative power, low degree of specialization of administrative management and unreasonable administrative organization structure. This paper innovates the management of colleges and universities, and reforms the university education in combination with the characteristics of the digital age. Based on the collaborative innovation theory of colleges and universities, this paper puts forward the collaborative management innovation network model of colleges and universities. The model combines the management theory with the practical research of collaborative innovation in colleges and universities, expands the application and research field of innovation network theory, constructs the evaluation index system of students' satisfaction in teaching management in colleges and universities, and discusses it through reading and consulting materials and communication with teachers and students. A questionnaire of college teaching management based on student satisfaction is formed. The experiment shows that the teaching satisfaction is improved by nearly 31% compared with that before the innovation and reform. It can initially get the effect of innovation and reform, meet the needs of students and promote the improvement of teaching management quality.